Influence of laser parameters on the stationary operation of a two-mode random.micro laser - Dinh, Van Hoang (H. : ĐHQGHN, 2017)
Solving the system of equations describing the stationary operation of a two-mode random microlaser we have found the transformation of saturated values of mode intensity when laser parameters as gain and loss coefficients as well as field coupling, photon hopping coefficients vary. From obtained results we determined which parameter takes the most important role for stationary operation of random microlasers.